THE PREVALENCE OF INTRA-SENTENTIAL SWITCHING IN SEPET MOVIE: REFLECTING MULTILINGUALISM REALITIES IN THE SOCIETY - Ni Wayan Yuni Lastari; Putu Devi Maharani (Lire Journal (Journal of Linguistics and Literature), 2026)
Code-switching is a common phenomenon now and has also entered the socio-cultural environment. Nowadays, code-switching is used in everyday speech, for instance, when producing a video or giving a formal presentation. The current research discusses language switching within a single sentence, or intra-sentential switching, in Yasmin Ahmad's movie Sepet (2004), which vividly presents Malaysia's multilingual society, including Malay, English, and Cantonese, seamlessly integrated into a single statement. The most frequent type of language switching was intra-sentential, indicating a very high degree of bilingual competence among speakers and the sociocultural reality of flexible identity negotiation in multicultural interaction. This research is focused on the analysis of syntactical units such as words, phrases, clauses, and language functions-for example, referential, expressive, and directive. The data were analysed using descriptive qualitative methods. This study has two objectives:(1) to characterize the syntactic units in the Sepet movie by Yasmin Ahmed, and (2) to examine language functions and matrix language used in the Sepet movie. Data indicate that people frequently communicate in a mix of languages. From the results of this study, it was found that film characters frequently used intra-sentence changes to communicate, and the most frequent language functions applied were referential, expressive, and directive. This reflects how these changes serve as a communicative strategy in cinematic discourse for linking up linguistic theory to real-world multilingual practices.